To solve the system of equations, we can substitute the value of y from the second equation into the first equation.
Substituting y=10+4x into the first equation, we get:
8x - 3(10+4x) = -22
Simplifying, we have:
8x - 30 - 12x = -22
Combining like terms, we get:
-4x - 30 = -22
Adding 30 to both sides:
-4x = 8
Dividing both sides by -4:
x = -2
Substituting this value of x into the second equation to find y:
y = 10 + 4(-2)
y = 10 - 8
y = 2
Therefore, the solution to the system of equations is x = -2 and y = 2.
Solve the system of equations
8x-3y=-22
y=10+4x
1 answer